Therapeutic Development of Mesenchymal Stem Cells or Their Extracellular Vesicles to Inhibit Autoimmune-Mediated Inflammatory Processes in Systemic Lupus Erythematosus - Sharma, Juhi; Hampton, Jeffrey M.; Valiente, Giancarlo R.; Wada, Takuma; Steigelman, Holly; Young, Matthew C.; Spurbeck, Rachel R.; Blazek, Alisa D.; Bösh, Steffi; Jarjour, Wael N.; Young, Nicholas A. (Frontiers in Immunology, 2017)
Since being discovered over half a century ago, mesenchymal stem cells (MSCs) have been investigated extensively to characterize their cellular and physiological influences. MSCs have been shown to possess immunosuppressive capacity through inhibiting lymphocyte activation/proliferation and proinflammatory cytokine secretion while simultaneously demonstrating limited allogenic reactivity, which subsequently led to the evaluation of therapeutic feasibility to treat inflammatory diseases. Although regulatory constraints have restricted MSC development pharmacologically, limited clinical studies have shown encouraging results using MSC infusions to treat systemic lupus erythematosus (SLE); but, more trials will have to be performed to conclusively determine the clinical efficacy of MSCs to treat SLE. Moreover, there is some data to suggest that MSCs possess tumorigenic potential and that the immunosuppressive influence can be dramatically affected by both donor variability and ex vivo expansion. Given that recent studies have found that the immunosuppressive effects of MSCs are a result, at least in part, to extracellular vesicle (EV) secretion, the use of MSC-derived EVs has been suggested as a cell-free therapeutic alternative. Despite the positive data observed using EVs isolated from human MSCs to suppress inflammatory responses in vitro and in inhibiting autoimmune disease pathogenesis in preclinical work, there are no studies to date examining EVs from MSCs to treat SLE in humans or animal models. Considering that EVs are not subject to the strict regulatory constraints of stem cell-based pharmacological development and are more readily standardized with regard to industrial scale production and storage, this review outlines the anti-inflammatory biology of MSCs and the scientific evidence supporting the potential use of EVs derived from human MSCs to treat patients with SLE.